Never fly solo : lead with courage, build trusting partnerships and reach new heights in business - Waldman, Rob (McGraw-Hill, 2010)
The New York Times and Wall Street Journal bestselling book on building powerful, effective teams! "An amazing book that bucks the old paradigm that maverick leaders and self-made entrepreneurs set the bar. It will forever change the way you look at leadership."--Marshall Goldsmith, author of The Wall Street Journal #1 business bestseller What Got You Here Won't Get You There "In Never Fly Solo, Rob 'Waldo' Waldman shares potent, personal leadership lessons on what it takes to access the power of your wingmen. If you want a former fi ghter pilot with 65 combat missions as your wingman and if business success is your target, take flight with Waldo's book and earn your wings. You'll never fly solo again." -Jeffrey Gitomer, bestselling author of The Little Red Book of Selling "If you are serious about building trusting relationships and launching your business and life to new heights, then invest in yourself and buy this book." -Keith Ferrazzi, author of the New York Times #1 bestseller Who's Got Your Back "Authentic and inspirational, Never Fly Solo is a winning formula for successful leadership that everyone in business should read." -Howard Putnam, former CEO of Southwest Airlines and author of The Winds of Turbulence "Waldo does a superb job of applying to the business world the lessons he learned in his military career. His excellent use of vignettes shows how standards and values are applicable to leading an honorable life." -General Ron Fogleman, U.S. Air Force Retired, former Chief of Staff, USAF "Waldo the Wingman knows the value of relationships and how to build real partnerships that benefit everyone involved." -Mark Sanborn, speaker and bestselling author of The Fred Factor and You Don't Need a Title to Be a Leader Rob "Waldo" Waldman understands one thing better than most businesspeople: You can't reach your highest potential alone. You need wingmen-trusted partners-who can help you overcome obstacles, adapt to change, and prepare for success. A decorated former combat F-16 fighter pilot and now a successful entrepreneur, Waldman lives his life by this rule. Whether you're a senior executive, mid-level manager, or new hire fresh out of college, your success depends on the mutual support of trusted associates. In Never Fly Solo, Waldo helps you maximize your relationships to reach your greatest potential. You'll learn how to: Commit to the core wingman values of integrity, accountability, service, and excellence Transform your relat ...